Perkuatan Lereng Pada Pengembangan Wisata Bukit Watu Belah di Kalurahan Banjarasri Kapanewon Kalibawang: Slope Reinforcement for the Development of Watu Belah Hill Tourism in Banjarasri Village Kapanewon Kalibawang - Tigo Mindiastiwi; Bambang Widodo (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
The village of Banjarasri, located in the Kapanewon Kalibawang district of Yogyakarta Special Region, has great natural potential that can be developed into a tourist destination. One of the planned locations is Watu Belah Hill. The purpose of this community service activity is to identify the existing conditions of the development of Watu Belah Hill tourism and provide effective planning recommendations for the site. The methods used in this community service activity are surveys, observations, planning, and socialization to the local village officials. Based on the survey and observation results, it is found that the slope condition at the location of Watu Belah Hill tourism development has a slope angle of 160-400 with moderate potential for landslides. The geotechnical team of this community service activity recommends slope reinforcement using terracing and gabion structures for the development of Watu Belah Hill tourism.